Total Cholesterol, Triglyseryda, and Coronary Hearth Disease Incidence in Hearth Polyclinic of dr. M. Yunus Hospital Bengkulu - Nurul Khairani; Awal Isgiyanto; Lilis Sumarni (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2018)
The impact of coronary heart disease (CHD) can cause heart failure and even a deadly heart attack. This study aimed to study the relationship of total cholesterol and triglyceride levels with CHD in patients visiting the Cardiac Polyclinic of Dr. M. Yunus Bengkulu. This type of research used Analytical Survey with Case Control design. The population in this study was all patients of the Cardiac Polyclinic of RSUD dr. M. Yunus Bengkulu. Case samples in this study were 84 patients with CHD and 84 controls were taken using a Systematic Random Sampling technique. The data in this study used secondary data and data analysis techniques using univariate, bivariate, and multivariate analysis. Data analysis in this study used Chi-Square test (c2). To determine the closeness of the relationship, the Contingency Coefficient (C) test was used. To find out the risk factors used the Odds Ratio (OR) test. The results obtained from 168 people there were 84 people (50.0%) who had CHD, 87 people (51.8%) had total cholesterol levels ≥ 200 mg / dL and 100 people (59.5%) who had triglyceride levels ≥ 150 mg / dL. There was a correlation between total cholesterol levels and triglyceride levels with CHD in patients who visited the Cardiac Polyclinic of dr. M. Yunus Bengkulu with a moderate relationship category. It is expected that health workers can increase information regarding the prevention and control of total cholesterol levels and triglyceride levels in CHD patients, and recommend to maintain a healthy lifestyle and exercise in order to improve the quality of life of patients with CHD.Keywords: coronary heart disease, total cholesterol levels, triglyceride levels,